How Could Self-Determination Theory Be Useful for Facing Health Innovation Challenges? - Migliorini, Laura; Cardinali, Paola; Rania, Nadia (Frontiers in Psychology, 2019)
This paper offers a presentation of the characteristics of self-determination theory (SDT) in the health context as well as attempts to identify how this theory could be useful for facing health innovation challenges. Health innovation is based on scientific advances that have more complex relationships with health. This paper encourages the use of the SDT approach to face health innovation, both for physiological and pathological processes. In particular, the focus is on the changes and lifestyle choices related to physiological pregnancy and birth and to oncological genetic tests in the Italian context. The health innovation paradigm focuses on patients taking responsibility for making important health-related choices, and we think that SDT can offer new stimuli in light of the changes implemented from innovations in the field of health. The aim is that this manuscript will stimulate researchers to test the potential of this theory in the field of changing health-related processes. Practitioners are called upon to revise their orientation toward patients and, according to SDT, they should support autonomy rather than control the promotion of health-related change.